Supervisee-supervisor relationship influences Second Language Writing Anxiety in postgraduate dissertation writing - Wan Safuraa Wan Osman,; Fatiha Senom,; Shanina Sharatol Ahmad Shah, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Since it is a social affair as it is cognitive, collaboration with supervisor is a central aspect of postgraduate dissertation writing. In this view, the research intends to offer insights on the underlying social transaction between supervisee and supervisor and how this may influence supervisee’s second language writing anxiety when writing. In this qualitative study, three Malaysian postgraduate students were asked to complete Cheng’s (2004) Second Language Writing Anxiety Inventory (henceforth, as SLWAI) before they were interviewed. The findings were generated using thematic analysis on the data of 91 interview questions and 22 items in the SLWAI, in which the self-assessment provides information on their tendencies for cognitive anxiety, somatic anxiety, and avoidance behaviours. The findings showed that the participants exhibited low-self-esteem, emotional distress, underdeveloped research ownership, negative self-perceptions, and negative perceptions towards dissertation writing, when exposed to anxiety-salient conditions such as receiving negative comments, perceiving external locus of control, and lacking rapport with supervisor. Under those circumstances, the participants appear to perceive their supervisors as examiners and as potential threat to their writing goal. In effect, the supervisors’ manipulation of anxiety to provoke performance and the perceived social distance tend to exacerbate their writing anxiety. Therefore, the study significance lies in its efforts to improve supervision, student’s motivation and performance in dissertation writing by promoting greater understanding of writing anxiety and supervisee-supervisor relationship. Thus, highlighting the interrelationship between the affective phenomenon and the social aspect of dissertation writing, the study also discusses theoretical, methodological, and pedagogical implications.